Evolution of early Eocene Palaeosinopa (Mammalia, Pantolestidae) in the Willwood Formation of the Bighorn Basin, Wyoming. (3rd November 2015) - Dunn, Rachel H.; Rose, Kenneth D.
Abstract: Species-level diversity and evolution of Palaeosinopa from the Willwood Formation of the Bighorn Basin is reassessed based on substantial new material from the Bighorn, Powder River, and Wind River basins. We recognize three species of Palaeosinopa in the Willwood Formation of the Bighorn Basin: P. lutreola, P. incerta, and P. veterrima . The late Wasatchian species P. didelphoides is not present in the Bighorn Basin. The Willwood species can be differentiated based only on size. P. veterrima is the most common and wide-ranging species and is the most variable in size and morphology: the stratigraphically lowest individuals are smaller, with narrower, more crestiform lower molars; whereas the highest are larger, with wider, more bunodont teeth. Although it could be argued that these represent distinct species, we demonstrate that this morphological evolution occurred as the gradual and mosaic accumulation of features, suggesting in situ anagenetic evolution. The two smaller species are present only low in the section (biochrons Wa0–Wa4) and show no discernable evolution in size or morphology. A new skeleton of Palaeosinopa veterrima from the Willwood Formation is described, and other new postcrania are reported. The skeleton is the oldest associated skeleton of Palaeosinopa known, yet it is remarkably similar to those of younger, more derived pantolestids, the primary disparities being minor differences in proportions of the innominate, femur, and tibia, and co-ossification of the distal tibia and fibula. Either P. incerta or P. lutreola was likely the ancestral population that gave rise to the other Wasatchian Palaeosinopa . Alternatively, P. veterrima may have migrated into the Bighorn Basin from the Powder River Basin.